Development of Mixed Autonomous Power System on the Basis of Renewable Energy Sources - D. P. Laoshvili; G. K. Kokhreidze (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A principal circuit diagram has been developed for an autonomous power system on the basis of renewable energy sources – solar and accumulator batteries.Due to the usage of a dc pulse converter, a dc converter (interrupter), an IGBT module inverter and a single-phase matching power transformer it is possible to achieve an effective sectioning of constant voltage and their inversion with minimal energy losses.Efficiency factor of the proposed converter installation exceeds 90 % and power factor is close to unity.